Determinanty stabilności finansowej sektora ubezpieczeń - Czerwińska, Teresa (Studia Oeconomica Posnaniensia, 2015)
The aim of the paper is to identify the key determinants for the stability of the insurance sector and to analyze possible consequences of implementing new macro-prudential regulation. We discuss the possible consequences of the implementation of solutions currently proposed for the insurance sector.